2022
DOI: 10.3390/microorganisms10020213
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Clostridium baratii Reveals Strain-Level Diversity in Toxin Abundance

Abstract: Clostridium baratii strains are rare opportunistic pathogens associated with botulism intoxication. They have been isolated from foods, soil and be carried asymptomatically or cause botulism outbreaks. Is not taxonomically related to Clostridium botulinum, but some strains are equipped with BoNT/F7 cluster. Despite their relationship with diseases, our knowledge regarding the genomic features and phylogenetic characteristics is limited. We analyzed the pangenome of C. baratii to understand the diversity and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
(131 reference statements)
2
4
0
Order By: Relevance
“…Furthermore, the fitted curve for the pangenome profile showed that the fitted exponent of the curve was positive, indicating that the pangenome of C. tyrobutyricum is open. This observation is in agreement with the few published reports on this topic on other members of the genus Clostridium cluster I ( Udaondo et al, 2017 ), such as Clostridium baratii ( Silva-Andrade et al, 2022 ), C. perfringens ( Kiu et al, 2017 ; Feng et al, 2020 ), C. beijerinckii ( Sedlar et al, 2021 ; Zou et al, 2021a ), and C. butyricum ( Zou et al, 2021b ). Open pangenomes may indicate the necessity of constant genomic adaptations and diversification to cope with heterogeneous environments ( Medini et al, 2005 ; Rouli et al, 2015 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the fitted curve for the pangenome profile showed that the fitted exponent of the curve was positive, indicating that the pangenome of C. tyrobutyricum is open. This observation is in agreement with the few published reports on this topic on other members of the genus Clostridium cluster I ( Udaondo et al, 2017 ), such as Clostridium baratii ( Silva-Andrade et al, 2022 ), C. perfringens ( Kiu et al, 2017 ; Feng et al, 2020 ), C. beijerinckii ( Sedlar et al, 2021 ; Zou et al, 2021a ), and C. butyricum ( Zou et al, 2021b ). Open pangenomes may indicate the necessity of constant genomic adaptations and diversification to cope with heterogeneous environments ( Medini et al, 2005 ; Rouli et al, 2015 ).…”
Section: Resultssupporting
confidence: 92%
“…The housekeeping COG categories included “amino acids transport and metabolism” (9.33%) “inorganic ion transport and metabolism” (6.14%), “energy production and conversion” (8.32%), and “coenzyme transport and metabolism” (5.46%). High abundance of these gene categories within the core genome indicates that the strains are metabolically similar, which is consistent with other clostridia, including C. butyricum , C. beijerinckii , C. sporogenes , and C. baratii , which have open pangenomes ( Wu et al, 2017 ; Sedlar et al, 2021 ; Zou et al, 2021b ; Silva-Andrade et al, 2022 ). Furthermore, genes from the category “translation, ribosomal structure and biogenesis” were also abundant in the core genome (1.59%).…”
Section: Resultssupporting
confidence: 74%
“…Frontiers in Microbiology frontiersin.org relatedness among isolates and allowing a deeper understanding of transmission dynamics, emerging clones, key virulence loci, and the presence of AMR genes (Salipante et al, 2015;Quainoo et al, 2017;Pightling et al, 2018). The pangenome analysis of C. perfringens conducted in this study showed an accessory genome of 97.32%, an extremely high percentage in comparison with other closely related bacteria such as C. paraputrificum, species with an accessory genome of 67%, C. tertium with 37.6% of accessory genes (Muñoz et al, 2019), or C. baratii with an accessory genome of 24.43% (Silva-Andrade et al, 2022). This high level of genome plasticity is similar to the one found in Clostridioides difficile, which has an accessory genome of 87.2% (Knight et al, 2021).…”
Section: Discussionmentioning
confidence: 49%
“…In addition to the detection of C. difficile in the direct environment of the patient, studies have also confirmed the presence of other pathogenic species, such as C. perfringens , C. sporogenes , C. innocuum and C. baratii . These are species which are also detected in other medical facilities and which may constitute a significant disease-causing problem related to HAI [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Analysis of the behaviour of hospital personnel was not a direct goal of this study, but it supplements the conducted research analyses.…”
Section: Discussionmentioning
confidence: 99%